Principles of creating a public transport network model for regions - Ranceva, Justina; Ušpalytė-Vitkūnienė, Rasa (International Conference “Environmental Engineering”, 2023)
This article analyzes one of the steps of the transportation system model - network modeling. The network model consists of: zoning of the considered region, selection of network connections and routes of public transport lines, choosing the demand time series of the model. The model created for the region has its own specificities, such as uneven population density, big differentiation of public transport demand in terms of place and time. Therefore, the development of a public transport model for a region is very different from a public transport model for a city. The purpose of this article is to determine the specifics of creating a regional network model. To achieve this goal, the article analyses the best features and principles of the components of the such kind network model.